Direct load control of residential water heaters - Torgeir Ericson (Statistics Norway, Research Department, 2006)
In Norway there is a growing concern that electricity production and transmission may not meet the demand in peak-load situations. It is therefore important to evaluate the potential of different demand side measures that may contribute to reduce peak load. This paper analyses data from an experiment where residential water heaters were automatically disconnected during peak periods of the day. A model of hourly electricity consumption is used to evaluate the effects on the load of the disconnections. The results indicate an average consumption reduction per household of approximately 0.5 kWh/h during disconnection, and an additional average increase in consumption the following hour, due to the payback effect, of approximately 0.2 kWh/h.
Keywords: D10; Q41; 330; Direct load control; Demand response; Load management; Water heaters